Local Rates and Housing Subsidies - Bowley, Marian (Review of Economic Studies, 1940)
Journal Article Local Rates and Housing Subsidies Get access Marian Bowley Marian Bowley Dundee Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 8, Issue 1, October 1940, Pages 33–44, https://doi.org/10.2307/2967415 Published: 01 October 1940